Network neutrality and the evolution of the internet - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2010)
In order to create incentives for Internet traffic providers not to discriminate with respect to certain applications on the basis of network capacity require-ments, the concept of market driven network neutrality is introduced. Its basic characteristics are that all applications are bearing the opportunity costs of the required traffic capacities. An economic framework for market driven network neutrality in broadband Internet is provided, consisting of congestion pricing and quality of service differentiation. However, network neutrality regulation with its reference point of the traditional TCP would result in regulatory micro-management of traffic network management.
Keywords: 330